2017
DOI: 10.1186/s13033-017-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

Training needs and perspectives of community health workers in relation to integrating child mental health care into primary health care in a rural setting in sub-Saharan Africa: a mixed methods study

Abstract: BackgroundCommunity health workers can help to address the substantial unmet need for child mental health care in low and middle income countries. However, little is known about their training needs for this potential role. The aim of this study was to examine training needs and perspectives of community health extension workers (HEWs) in relation to providing child mental health care in rural Ethiopia.MethodsThe study was conducted in the Southern Nations, Nationalities and Peoples’ Region of Ethiopia. A mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…CHWs in these studies completed secondary school and were trained in communication skills, psychoeducation on perinatal depression, and intervention technique using stress/anger management [ 14 ] and/or cognitive behaviour therapy [ 16 ]. However, very few studies have investigated the personal characteristics and competencies required for CHWs to carry out these tasks [ 17 , 18 ] despite acknowledgement that knowledge to specific mental health issues and communication skills is important in improving competencies to deliver support.…”
Section: Introductionmentioning
confidence: 99%
“…CHWs in these studies completed secondary school and were trained in communication skills, psychoeducation on perinatal depression, and intervention technique using stress/anger management [ 14 ] and/or cognitive behaviour therapy [ 16 ]. However, very few studies have investigated the personal characteristics and competencies required for CHWs to carry out these tasks [ 17 , 18 ] despite acknowledgement that knowledge to specific mental health issues and communication skills is important in improving competencies to deliver support.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges facing CHW programs is the maintenance of skills and knowledge [ 7 , 8 , 27 ]. The traditional approach to training involves CHWs attending a 5-day in-person iCCM training course often held in a central location.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the need for refresher training, many challenges surround its provision, including a shortage of trained personnel to deliver training, lack of attention from government-level policy makers, financial constraints and long gaps between initial and refresher training [ 7 , 8 ]. Lack of refresher training is one factor that has been identified as contributing to the failure of CHW programs over time [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shibre et al , 2006 ) indicated that completion of a questionnaire through a face-to-face interview with a lay interviewer is a culturally appropriate alternative. The local researchers in our team guided the design of these study aspects, including appropriate training for the lay interviewers (Tilahun et al , 2017a , b ).…”
Section: The Case For Using Local Expertisementioning
confidence: 99%